(untitled) (Research, Society and Development, 2022)
A bodybuilding athlete to compete must present a set of characteristics to be evaluated. For these attributes to be presented within the required standard, there is a need for specific diets. Based on this premise, the objective of this article was to expose, through an integrative review of the literature, the complexity of the diet intended for bodybuilding athletes. To achieve the proposed objective, a descriptive literature review was applied. In order to explore and carry out the data collection that was carried out in books and scientific articles. Based on the data collected, it is clear how complex the diet intended for bodybuilding athletes is. For these athletes, limited and balanced nutrition is required in conjunction with training. Considering that the objective of these athletes is not only muscular hypertrophy, but also the definition of the body. Since the preparation of a bodybuilder goes through several phases, it is worth considering the specificity of each of these steps so that the correct nutritional strategies are taken to meet each phase of preparation. It is worth mentioning that bulking/off is characterized by the constant excesses of the athletes’ routine seeking maximum gains in muscle volume. Therefore, it is at this stage that athletes increase their calorie intake beyond recommended levels. During the cutting/pre-contest, excess food is left behind and a restrictive diet becomes part of the daily life of bodybuilders.